Recent Advances in Catalytic Stereocontrolled Cycloaddition with Terminal Propargylic Compounds - Hu, Xin-Hu; Liu, Zhen-Ting; Shao, Long; Hu, Xiang-Ping (Synthesis, 2015)
Terminal propargylic compounds containing an alkyne unit and an alcohol or ester group in the propargylic position have a fairly acidic acetylenic hydrogen atom; this makes them versatile substrates for further chemical transformation. Some transition metals such as ruthenium or copper exhibit specific affinity for terminal propargylic compounds, generating dielectrophilic ruthenium– or copper–allenylidene complexes that show high potential for stereoselective cycloaddition with various bis-nucleophiles. In this review, we highlight this emerging field of catalytic stereoselective cycloaddition with terminal propargylic compounds. Examples of ruthenium-, copper-, palladium-, and gold-catalyzed cycloaddition are given in the article, along with mechanistic considerations.1 Introduction2 Ruthenium–Allenylidene Complexes in Enantioselective Cycloaddition3 Copper–Allenylidene Complexes in Enantioselective Cycloaddition4 Palladium–π-Propargyl Complexes in Stereoselective Cycloaddition5 Gold–Carbenoid Complexes in Stereoselective Cycloaddition6 Summary and Outlook
Keywords: cycloaddition; asymmetric catalysis; propargylic compound; ruthenium; copper; palladium; gold